Pohon Zaitun dalam al-Qur’an: Studi Tafsir Maudhu’i Abdul Hay al-Farmawi - Saputra, Teguh; Rusmana, Dadan (Jurnal Riset Agama, 2021)
The purpose of this study is to discuss the olive tree in the Qur'an. This research method uses a type of qualitative research through a literature study approach and the thematic interpretation method initiated by Abdul Hay al-Farmawi. Then this study applies content analysis as a tool to explore the collected data so that it can lead to conclusions with a multidisciplinary approach in the form of health sciences. The results and discussion of this study are olive trees have green leaves, the trunk is golden brown, about 3 to 15 meters high, the flowers are white or cream, the fruit is light green but when very ripe it turns purple, long-lived because able to survive in a relatively long period of time and this olive tree grows, including in Africa, Arabia, India and Asia. Then the olive tree is mentioned 7 times in the Qur'an, namely 6 times with the word olive and 1 time with the word thursina. And the olive tree has many benefits, especially for health, such as the fruit which has a high enough protein content so it is good for consumption and can increase appetite and the oil can be used to nourish the skin and hair. This study concluded that the olive tree is a tree that is very beneficial for health. So it is appropriate for us to maintain and preserve a variety of existing trees, especially olive trees by preserving and preserving the natural environment. This study recommends that research be conducted on other trees in the Qur'an, such as date palms, grapes or khuldi.